Cause-specific mortality in the general population with transient dipstick-proteinuria - Nagai, Kei (PLoS One, 2019)
Recently, changes in urinary albumin and in GFR have been recognized as risk factors for the development of end-stage kidney disease and mortality. Though most clinical epidemiology studies of chronic kidney disease (CKD) used renal function and proteinuria at baseline alone, definitive diagnosis of CKD with multiple measurements intensifies the differences in the risk for mortality between the CKD and non-CKD populations. We hypothesized that a transient diagnosis of proteinuria and reduced renal function each indicate a significantly higher mortality compared to definitive non-CKD as the negative control and lower mortality compared with definitive CKD as the positive control. The present longitudinal study evaluated a general-population cohort of 338,094 persons who received annual health checkups, with a median 4.3-year study period. There were 2,481 deaths, including 510 CVD deaths (20.6%) and 1,328 cancer deaths (53.5%), and mortality risk was evaluated for transient proteinuria and for transiently reduced renal function. The hazard ratios (HRs) for all-cause mortality and cancer mortality were not significant, but that for cardiovascular mortality was significantly higher for transient proteinuria (HR, 1.94 [95% confidence interval, 1.27–2.96] in men and 2.78 [1.50–5.16] in women). On the other hand, transiently reduced renal function was not significant for either cardiovascular mortality risk or cancer mortality risk. We surmise that this is the first study of the mortality risk of transient dipstick proteinuria in a large general-population cohort with cause-specific death registration. Transiently positive proteinuria appears to be a significant risk specifically for cardiovascular mortality compared with definitely negative for proteinuria.